2015
DOI: 10.1038/ejcn.2014.276
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and vegetable intake and mortality from cardiovascular disease in Japan: a 24-year follow-up of the NIPPON DATA80 Study

Abstract: The results showed that higher total intake of FVs was significantly associated with reduced risk of CVD mortality in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 40 publications
1
49
1
Order By: Relevance
“…Vegetable protein intake (continuous value) showed inverse relationships with mortality for almost all CVD subtypes irrespective of the presence of hypertension. We also observed significant relationual in this analysis 28,[30][31][32] . A limited number of nutrients were calculated in the NNSJ 90, and vegetable protein intake was not included 28) .…”
Section: Resultssupporting
confidence: 76%
“…Vegetable protein intake (continuous value) showed inverse relationships with mortality for almost all CVD subtypes irrespective of the presence of hypertension. We also observed significant relationual in this analysis 28,[30][31][32] . A limited number of nutrients were calculated in the NNSJ 90, and vegetable protein intake was not included 28) .…”
Section: Resultssupporting
confidence: 76%
“…As a result, the point estimate remarkably increased after adjustment for vegetable intake, especially in men. Several studies have shown that a lower mortality risk is associated with a higher vegetable intake, including previous our study, which had a same dataset as that of the present study 18,[39][40][41][42] . An increase in total energy intake also increases vegetable intake because of the increase in absolute intake.…”
Section: Baseline Characteristics By Quintiles Of Total Energy Intakementioning
confidence: 68%
“…Detailed methods of NNSJ and estimation of individual intake of nutrients and food groups are described elsewhere 18,21,22,27,28) . A food intake survey was conducted using the weighing record method for 3 consecutive days in each household by trained interviewers.…”
Section: Nutritional Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed that an animal-based LCD was associated with all-cause mortality, whereas a LCD based on vegetable sources has a protective effect for all-cause mortality [8]. In this study, intake of carbohydrate to fiber ratio has a positive correlation with PRAL or NEAP, which has been known to be a risk factor for hypertension [24], type 2 diabetes [25, 26], and MetS [27]; and has a negative correlation with fruit and vegetable intake [28, 29], which has a protective effect on human health. On the other hand, the association between carbohydrate intake and this nutrition was not consistent.…”
Section: Discussionmentioning
confidence: 94%